The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.21203/rs.3.rs-45708/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of Socio-Economic and Demographic Factors on Health Seeking Behavior of Urban Households, Bangladesh

Abstract: Aim: As households’ health-seeking behavior depends enormously on socio-economic and demographic factors particularly in developing county like Bangladesh, it contributes differently to health-care seeking behavior varying household to household. This study intends to explore the nature of the health seeking behavior of urban residents in Sylhet city through assessing the socio-economic and socio-demographic factors. Subject and Methods: A 150 household survey has been completed in Sylhet city, using a multist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
(12 reference statements)
0
0
0
Order By: Relevance
“…Studies have shown that highincome earners are more likely than low-income earners to seek health care early, particularly where there is no universal health care coverage. 27 As found in other studies, infection risks are also associated with the occupation. In Wave 1, the risk of infection was significantly higher in the so-called first-line workers, including in Health, Education, Police Services and Correctional Services.…”
Section: Incidence Rates and Relative Riskmentioning
confidence: 54%
“…Studies have shown that highincome earners are more likely than low-income earners to seek health care early, particularly where there is no universal health care coverage. 27 As found in other studies, infection risks are also associated with the occupation. In Wave 1, the risk of infection was significantly higher in the so-called first-line workers, including in Health, Education, Police Services and Correctional Services.…”
Section: Incidence Rates and Relative Riskmentioning
confidence: 54%